Human Machine Interface Based on Eye Wink Detection - Kiran P; Mohana HS; Vijaya PA (International Journal of Informatics and Communication Technology (IJ-ICT), 2013)
The research of human-computer interfaces has become a growing field in computer science, which aims to attain the development of more natural, intuitive, unobtrusive and efficient interfaces. The present work describes a Human Machine Interface Based on Eye Wink Detection for helping the severely handicapped people to manipulate the household devices and to perform day to day activities. Algorithm for eye detection that is conductedthrough a process of extracting the face image from the video image followed by evaluating the eye region and then eventually detecting the eye state based on skin colour segmentation. Binary values 1 and 0 is assigned based on the opening and closing of eye. Finally applying the dynamic programming to translate the code sequences to a certain valid command. Experiment conducted for different test video displayed significant results which is carried out with different set of inputs.DOI: http://dx.doi.org/10.11591/ij-ict.v2i2.3927